2013
DOI: 10.3748/wjg.v19.i40.6794
|View full text |Cite
|
Sign up to set email alerts
|

Gut-lung crosstalk in pulmonary involvement with inflammatory bowel diseases

Abstract: Pulmonary abnormalities, dysfunction or hyper-reactivity occurs in association with inflammatory bowel disease (IBD) more frequently than previously recognized. Emerging evidence suggests that subtle inflammation exists in the airways among IBD patients even in the absence of any bronchopulmonary symptoms, and with normal pulmonary functions. The pulmonary impairment is more pronounced in IBD patients with active disease than in those in remission. A growing number of case reports show that the IBD patients de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 108 publications
0
63
0
Order By: Relevance
“…These novel data, along with increased awareness of potential linkbetween asthma (where HDM is clearly implicated) and IBD,37 it is tempting to speculate a central role of HDM in the link between these two diseases. In addition, we can envisage that HDM effect may be potentiated in inflammatory conditions where lower GIT becomes susceptible to IgE-mediated responses 38 39.…”
Section: Discussionmentioning
confidence: 99%
“…These novel data, along with increased awareness of potential linkbetween asthma (where HDM is clearly implicated) and IBD,37 it is tempting to speculate a central role of HDM in the link between these two diseases. In addition, we can envisage that HDM effect may be potentiated in inflammatory conditions where lower GIT becomes susceptible to IgE-mediated responses 38 39.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome residing on various mucosal surfaces plays a central role in health and disease (1,58,127). While much is known about gut microbiome, fecal microbial transplant (FMT) has been used only in the context of difficult gut infections like Clostridium difficile, and that too in an effective, yet simple approach, where "normal" microbiota is obtained from an identified and monitored cohort of individuals and cryopreserved for future FMT applications (128)(129)(130)(131)(132).…”
Section: Microbial Manipulationsmentioning
confidence: 99%
“…The reviews of the underlying mechanisms that can explain the association between the two chronic inflammatory conditions point towards systemic inflammation and immunological dysfunctions [9,10] triggered by environmental factors that IBD and COPD seem to share, such as smoking [25,26] or air pollution [27,28]. Furthermore, pulmonary involvement [29][30][31] is a common extra-intestinal manifestation of IBD and an increased intestinal permeability, one of the factors that may increase susceptibility to develop IBD, was described in COPD patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…While the association with neoplasms and cardiovascular diseases has been extensively explored, along with the role of cigarette smoke and systemic inflammation in the pathogenesis of these conditions, other comorbid conditions have received far less attention. COPD has been shown to be associated with other chronic inflammatory diseases, such as inflammatory bowel disease (IBD) [9,10]. Epidemiological studies have shown significant increases in incidence [11] and prevalence [12,13] of IBD in patients with airway diseases.…”
Section: Introductionmentioning
confidence: 99%